(untitled) (Scientific journal of the Fergana State University, 2024)
Linguistic genderology, which is recognized as new in world linguistics, has passed its development stage as a component of the anthropocentric paradigm. In many research works in linguistics, it has its own methodology, the terminological system of linguo-genderology has been developed. The theoretical issues of this field of science were considered in the scientific research conducted by foreign linguists and were approved by scientists.